Primary vs redo robotic pyeloplasty: A comparison of outcomes. Issue 4 (August 2021) - Mittal, Sameer; Aghababian, Aznive; Eftekharzadeh, Sahar; Dinardo, Lauren; Weaver, John; Weiss, Dana A.; Long, Christopher; Srinivasan, Arun K.; Shukla, Aseem R.
Summary: Introduction: Robot-assisted laparoscopic pyeloplasty (RALP) is a safe and efficacious option for repair of UPJO. We hypothesize that redo-RALP is technically more difficult but has comparable outcomes to primary RALP. Methods: An IRB-approved single institutional registry was utilized to identify all patients undergoing primary or redo RALP from 2012 to 2019. Redo RALP consisted of pyeloplasty and ureterocalicostomy (RALUC). Peri-operative and post-operative details and outcomes were aggregated. Successful reconstruction was defined as resolution of symptoms, improved hydronephrosis and no need for additional procedures. Results: From 399 patients who underwent UPJO repair at our center, a total of 306 with a median age of 4.9 years at surgery and a median follow-up of 18.5 months were included: 276 primary and 30 redo (21 RALP and 9 RALUC). Redo group had significantly longer procedure time and length of stay compared to the primary group. However, no significant difference was noted in the post-operative complications, need for additional endoscopic procedures or redo reconstruction, and success between the two groups. Multivariate analysis showed that when controlled for age, gender, 30-days post-operative complication and anatomy of obstruction, redo as compared to primary reconstruction did not have a significant effect on success. Discussion: This study is the largest controlled cohort in the pediatric population comparing redo RALP with an established control group -primary RALP. This retrospective chart review possesses the biases innate to any retrospective study. The low number of re-operative cases as well as low rate of failure in redo RALP further complicates identification of statistically significant predictors of outcomes following redo RALP. Conclusion: Redo RALP is an efficient and safe approach for reconstruction of recurrent UPJO, with low complication rate and high success rate, comparable to primary RALP.